KUALITAS UDARA DAN POTENSI TRANSMISI COVID-19 DI PULAU JAWA - Rizky Zulkarnain; Karuniawati Dewi Ramadani (Seminar Nasional Official Statistics, 2020)
The spreading of SARS-CoV-2 in Indonesia is increasingly worrying. COVID-19 pandemic has disrupted people’s lives, not only infected people but also the collateral survivors, that is people who are not infected but suffer disruption in their life due to a crisis. Java island is the epicenter of COVID-19 transmission in Indonesia. Several studies have shown that the incidence of COVID-19 has strong connections with the concentration of particulate matter in air. This study investigates the relationship between air quality and the risk of COVID-19 transmission in Java. Air quality is represented by NO2 concentration, while the risk of COVID-19 transmission is measured using COVID-19 Vigilance Index. This paper employs four models to identify the effect of NO2 exposure to the risk of COVID-19 transmission, where the population density is incorporated as control variable. Model-0 is the base model without cluster and spatial effects. Model-1 is the extension of Model-0 by adding spatial effect. Model-2 is the extension of Model-0 by adding cluster effect. While Model-3 is the complete model with spatial and cluster effects. The results showed that Model-3 is the best model in terms of explaining the relationship between NO2 concentration and the COVID-19 Vigilance Index. Model-3 improves the performance of base model substantially. Furthermore, estimation results suggest that NO2 concentration has positive connections with COVID-19 Vigilance Index, after cluster and spatial effects are considered. Regions with higher NO2 concentration (worse air quality) tend to have higher COVID-19 Vigilance Index (higher risk of COVID-19 transmission). These results have important implications for the mitigation strategies needed to handle COVID-19 transmission, especially in regions that have poor air quality.